Peningkatan Hasil Belajar PAI Siswa Kelas VII di SMP Negeri 3 Ampek Angkek Berbantuan Media Kuis Kahoot - Azmi, Annisa; Rahman, Yulia; Nurlina, Selfatima (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research was structured with the aim of improving student learning outcomes by using the Kahoot quiz media for class VII students of SMP Negeri 3 Ampek Angkek, Tanah Nyariang, Batu Taba for the 2022/2023 Academic Year. This type of research is Classroom Action Research (CAR), in which the researcher is the implementer of the lesson while the teacher is the observer. The subjects of this study were class VII students of SMP Negeri 3 Ampek Angkek consisting of 32 students. The object in this research is student learning outcomes. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in student learning outcomes, first; the learning outcomes of students' Islamic religious education subjects before utilizing the Kahoot quiz media in class VII of SMP Negeri 3 Ampek Angkek were low, out of 32 students only 46.87% or 15 students whose grades were above the minimum completeness criteria, while 53.12% or 17 other students scored below the minimum completeness criteria with an average of 62.5. Second, after using the Kahoot quiz media, student learning outcomes have increased in each cycle. In cycle I, the learning outcomes of students' Islamic religious education after using the Kahoot quiz media increased from pre-cycle with a completeness of 78.12%. Whereas in cycle II, the percentage of completeness was 100%. The use of the Kahoot quiz media can improve the learning outcomes of Islamic religious education subjects for class VII students of SMP Negeri 3 Ampek Angkek each cycle by 26.57%.